INFLUENCE OF THE VISCOUS FILLING ON A MOTION OF THE PRECESSING VESSEL - Гураль, Інеса Михайлівна; Наквасюк, Юлія Анатоліївна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The problem for determining the steady relative motion of a viscous incompressible fluid entirely filling a long cylindrical vessel executing regular precession with a small angle of nutation and / or with a small ratio of the angular precession velocity to the angular velocity of spin about the cavity axis is considered. Higher approximations of the expansion in a small parameter of the solution of the nonlinear Navier-Stokes equations and of the projection on the axis of the cylinder of the moment of the forces exerted by fluid on the lateral surface of the vessel are obtained.